Strategic enablers towards sustainable performance in Palestinian manufacturing SMEs: A mediator of strategic flexibility and a moderator of turbulent environment - Dwikat, Said Y. S. (2023)
The contribution of Small and Medium Enterprises (SMEs) to economic prosperity is widely acknowledged worldwide. However, the empirical evidence in the literature on enhancing sustainable performance in manufacturing industries in developing countries is still insufficient. Referring to the theory of Triple Bottom Line (TBL), Contingency Theory (CT) and Resource Based View (RBV), this study mainly aims to explore the influence of systematic strategic planning, strategic business innovation, and competent human capital on the sustainable performance of the manufacturing SMEs in Palestine as well as the mediation influence of strategic flexibility and the moderating influence of turbulent environment. The study was motivated by the inconsistent findings and gaps in the existing literature. Most prior studies focused on studying the conventional performance of SMEs, which is economic performance, while this study focused on studying sustainable performance, which includes social, environmental, and economic performance. Data were obtained among 235 owners and directors from manufacturing SMEs operating in Palestine via a random sampling technique. The analysis of results via the Partial Least Square Structural Equation Modelling (PLS-SEM) approach revealed that systematic strategic planning, strategic business innovation, and competent human capital positively influenced the sustainable performance of manufacturing SMEs. Meanwhile, mixed results were found upon investigating the mediating influence of strategic flexibility and the moderating influence of a turbulent environment. Strategic flexibility mediated all the relationships except the link between competent human capital and SMEs' sustainable performance. At the same time, the turbulent environment moderated only the relationship between systematic strategic planning and SMEs' sustainable performance. Lastly, the study provides key insights for directors, policymakers, and researchers on systematic strategic planning, strategic business innovation, competent human capital, strategic flexibility, turbulent environment, and sustainable performance. The study also discussed the limitations and outlined recommendations for future studies.